The Asymptotic Behavior of the Binomial Coefficients. Issue 2 (1st April 2017) - Levrie, Paul
Summary: In this note we give a rigorous proof by elementary means of the asymptotic behavior of the binomial coefficients. As an application we look at the convergence of the binomial series at the endpoints of the convergence interval.